Adsorção de cobre e cromo utilizando fibra de sisal visando o tratamento da água produzida pela indústria petrolífera - Borba, Loiva Liana Santos (2010)
Currently, the oil industry is the biggest cause of environmental pollution. The objective was to reduce the concentration of copper and chromium in the water produced by the oil industry. It was used as adsorbent natural sisal fiber Agave sp treated with nitric acid and sodium hydroxide. All vegetable fibers have physical and morphological properties that enablies the adsorption of pollutants. The basic composition of sisal is cellulose, hemicellulose and lignin. The features are typically found in the characterization of vegetable fibers, except the surface area that was practically zero. In the first stage of adsorption, it was evaluated the effect of temperature and time skeeking to optimize the execution of the factorial design. The results showed that the most feasible fiber was the one treated with acid in five hours (30°C). The second phase was a factorial design, using acid and five hours, this time was it determined in the first phase. The tests were conducted following the experimental design and the results were analyzed by statistical methods in order to optimize the main parameters that influence the process: pH, concentration (mol / L) and fiber mass/ metal solution volume. The volume / mass ratio factor showed significant interference in the adsorption process of chromium and copper. The results obtained after optimization showed that the highest percentages of extraction (98%) were obtained on the following operating conditions: pH: 5-6, Concentration: 100 ppm and mass/ volume: 1 gram of fiber/50mL solution. The results showed that the adsorption process was efficient to remove chromium and copper using sisal fibers, however, requiring further studies to optimize the process.